Pemaknaan Khalayak terhadap Kesenjangan Sosial Yang Ditunjukan Pada Film “Parasite” - Giselle Vincentia Tiogas; Lusia Savitri Setyo Utami (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2020)
For some countries including Indonesia, the problem of poverty has become one of the problems that are quite serious. With the existence of the problem of poverty resulted in a very striking social inequality in which some people live with all its abundance, while some other people live in inadequacy. Social inequality is not only found in the lives of Indonesian people, but can also be found in the lives of South Korean people as showed in the